Short-circuit-proof all-solid-state battery and preparation method thereof

By controlling the edge of the negative electrode plate to be located in the insulating coating of the positive electrode plate in an all-solid state battery and injecting composite insulating glue on the side of the core, the short circuit problem caused by the cracks and debris of the electrode plate is solved, and the safety and manufacturing efficiency of the battery are improved.

CN119695242APending Publication Date: 2025-03-25SODIUM TECHNOLOGY CO
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411842300.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The electrode plates of all-solid state batteries are prone to cracks and debris under isostatic pressure, resulting in direct contact between the positive and negative electrodes, causing short circuits, which leads to degradation of battery performance, thermal runaway or fire.

Method used

By controlling the edges of both ends of the negative electrode plate to be located in the insulating coating of the positive electrode plate and injecting composite insulating glue on the side of the core, short circuits caused by burrs and edge ruptures are reduced or avoided.

Benefits of technology

It effectively improves the safety of the battery, reduces the risk of thermal runaway and fire caused by short circuits, and simplifies the battery manufacturing process and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695242A_ABST
    Figure CN119695242A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-short-circuit all-solid-state battery and a preparation method thereof, and belongs to the technical field of solid-state batteries. The short-circuit-proof all-solid-state battery comprises a core body, wherein the core body comprises a positive pole piece, a solid electrolyte layer and a negative pole piece which are sequentially stacked; the positive pole piece comprises a positive current collector, a positive active material coating and insulating coatings, and the insulating coatings are positioned at the upper end and the lower end of the positive active material coating; the negative pole piece comprises a negative current collector and a negative active material coating; the upper end part and the lower end part of the negative active material coating are respectively positioned in the two insulating coating areas of the positive pole piece; the two sides of the core body in the length direction are provided with composite insulating rubber layers. By controlling the edges of the two ends of the negative pole piece to be located in the insulating coating of the positive pole piece and injecting the composite insulating glue into the side surface of the core body, the possibility of short circuit of the battery caused by burrs, edge breakage and the like of the solid-state battery pole piece is effectively reduced or avoided, so that the safety of the battery is improved; and thermal runaway and fire risks caused by short circuit are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a short-circuit-proof all-solid-state battery and a preparation method thereof. Background Art

[0002] With the growing demand for energy and the improvement of environmental awareness, all-solid-state batteries (ASSBs) are regarded as a strong candidate for the next generation of energy storage technology due to their advantages such as high energy density, high safety and long cycle life. All-solid-state batteries use solid electrolytes to replace the liquid electrolytes in traditional lithium-ion batteries, thereby eliminating the risks of leakage, volatilization and thermal runaway that may be caused by liquid electrolytes, significantly improving the safety of the battery. In addition, the use of solid-state electrolytes also provides greater flexibility in battery design, allowing the battery to operate in a wider temperature range and achieve higher energy density.

[0003] All-solid-state batteries are batteries that use solid electrolytes. Since all-solid-state batteries use solid electrolytes instead of liquid organic electrolytes, the safety performance of the battery is greatly improved. However, due to the rigidity and brittleness of the solid electrolyte, the pole pieces of the all-solid-state battery are prone to cracks and debris under isostatic pressing conditions. These cracks and debris may penetrate the electrolyte layer, resulting in direct contact between the positive and negative electrodes, thereby causing a short circuit. In addition, solid-state batteries in the prior art usually adopt a method of applying a solid electrolyte to the surface of the positive electrode sheet and then assembling it with the negative electrode sheet to form a battery, and the die-cutting area of ​​the negative electrode sheet in the traditional lithium-ion battery pole sheet production process is larger than the die-cutting area of ​​the positive electrode sheet. However, since burrs are formed on the edge of the pole sheet during the die-cutting process, the burrs on the edge of the positive electrode sheet with a smaller area are directly overlapped on the negative electrode sheet, which will cause the battery insulation to decrease or a short circuit risk to occur. Short circuits not only lead to a decrease in battery performance, but may also cause thermal runaway or fire, and even cause safety accidents. In order to solve this problem, patents CN118213607A and CN115513532A disclose a design method similar to an insulating ring, but this method is complex in design and manufacture and is not suitable for large-scale industrial production. Summary of the invention

[0004] In order to overcome the shortcomings of the prior art, one of the objects of the present invention is to provide a short-circuit-proof all-solid-state battery. The all-solid-state battery controls the edges of the two ends of the negative electrode plate to be located within the insulating coating of the positive electrode plate, and injects composite insulating glue on the side of the core body, thereby effectively reducing or avoiding the possibility of battery short circuit due to burrs, edge ruptures, etc. of the solid-state battery plate, thereby improving the safety of the battery and reducing the risk of thermal runaway and fire caused by short circuit.

[0005] To solve the above problems, the technical solution adopted by the present invention is as follows:

[0006] A short-circuit-proof all-solid-state battery, comprising a core body, wherein the core body comprises a positive electrode sheet, a solid electrolyte layer and a negative electrode sheet stacked in sequence;

[0007] The positive electrode plate includes a positive electrode current collector and a positive electrode active material coating and an insulating coating formed on the surface of the positive electrode current collector, wherein the insulating coating is located at the upper and lower ends of the positive electrode active material coating; the negative electrode plate includes a negative electrode current collector and a negative electrode active material coating formed on the surface of the negative electrode current collector;

[0008] The upper and lower ends of the negative electrode active material coating are respectively located in the two insulating coatings;

[0009] The core body is provided with composite insulating adhesive layers on both sides in the length direction.

[0010] As a preferred embodiment of the present invention, the length a of the negative electrode active material coating and the length a' of the positive electrode active material coating and the length c' of the insulating coating have the following relationship: a'<a<a'+2c; the width b of the negative electrode active material coating and the width b' of the positive electrode active material coating have the following relationship: b'<b.

[0011] Further preferably, the length a of the negative electrode active material coating and the length a' of the positive electrode active material coating have the following relationship: a-a'=2-4 mm. The width b of the negative electrode active material coating and the width b' of the positive electrode active material coating have the following relationship: b-b'=1-3 mm. The length c' of the insulating coating is 2-6 mm.

[0012] As a preferred embodiment of the present invention, the positive electrode current collector is one of aluminum foil, copper foil and steel foil. Further preferably, the aluminum foil is one of microporous aluminum foil, corroded aluminum foil and composite aluminum foil; the copper foil is one of microporous copper foil, corroded copper foil and composite copper foil; the steel foil is one of microporous steel foil and corroded steel foil.

[0013] As a preferred embodiment of the present invention, the positive electrode active material coating includes a positive electrode active material, a conductive agent, a solid electrolyte, and an adhesive. Further preferably, the positive electrode active material includes at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, layered sodium oxide, and sodium iron pyrophosphate; the conductive agent contains at least one of conductive layered graphite, conductive carbon black, VGCF, and CNT; the adhesive includes at least one of PVDF and PTFE. The solid electrolyte includes at least two of an oxide solid electrolyte, a sulfide solid electrolyte, and a polymer solid electrolyte. Among them, the oxide solid electrolyte includes but is not limited to Li 1.3 Al 0.3 Ti 1.7 (PO4)3(LATP), Li1.5 Al 0.5 Ge 1.5 (PO4)3(LAGP), Li7La3Zr2O 12 (LLZO), Li 6.55 Ga 0.15 La3Zr2O 12 , Li 1.5 Al 0.5 Ge 1.5 (PO4)3; sulfide solid electrolytes are Li2S-P2S5, Li2S-P2S5-LiCl, Li2S-P2S5-H2S, Li2S-P2S5-H2S-LiCl, Li2S-GeS2-Ga2S3, Li2S-GeS2-P2S5, Li2S-GeS2-Sb2S5, Na3PS4, Na3SbS4, Na2S-P2S5, Na 11 Sn2PS 12 At least one of the following: the polymer solid electrolyte is at least one of PEO, PAN, PMMA, and PVDF-HFP.

[0014] As a preferred embodiment of the present invention, the insulating coating comprises an adhesive, an inorganic oxide and an insulating paint, and the mass percentages of the adhesive, the inorganic oxide and the insulating paint are 10% to 30%: 40% to 50%: 30% to 40%.

[0015] As a preferred embodiment of the present invention, the molecular weight of the adhesive in the insulating coating is 500,000 to 1,000,000, and the adhesive is at least one of PVDF, PAA, and PVA; the inorganic oxide is nano-alumina and / or nano-ceramic powder; and the insulating paint is at least one of polyester resin, polyacetylphthalimide resin, polyurethane, and epoxy resin.

[0016] As a preferred embodiment of the present invention, the thickness of the insulating coating is the same as the thickness of the positive electrode active material coating; the thickness of the insulating coating is 50 to 500 um.

[0017] As a preferred embodiment of the present invention, the negative electrode current collector is one of aluminum foil, copper foil and steel foil. Further preferably, the aluminum foil is one of microporous aluminum foil, corroded aluminum foil and composite aluminum foil; the copper foil is one of microporous copper foil, corroded copper foil and composite copper foil; the steel foil is one of microporous steel foil and corroded steel foil.

[0018] As a preferred embodiment of the present invention, the negative electrode active material coating includes a negative electrode active material, a conductive agent, a binder and a solid electrolyte. The negative electrode active material includes at least one of graphite, nano-silicon, hard carbon and soft carbon; the conductive agent includes at least one of conductive layered graphite, conductive carbon black, VGCF and CNT; the binder includes at least one of PVDF and PTFE; the solid electrolyte includes at least two of oxide solid electrolyte, sulfide solid electrolyte and polymer solid electrolyte.

[0019] As a preferred embodiment of the present invention, the solid electrolyte layer includes a solid electrolyte, an inorganic sodium salt / lithium salt, and a binder.

[0020] As a preferred embodiment of the present invention, the composite insulating adhesive layer includes nano inorganic oxides, glass fibers, nitrides / carbides, and adhesives, and the mass percentages of the nano inorganic oxides, glass fibers, nitrides / carbides and adhesives are 30% to 40%: 20% to 30%: 10% to 20%: 20% to 30%.

[0021] Further preferably, the nano inorganic oxide is at least one of Al2O3, TiO2, and MgO; the "nitride / carbide" is nitride or carbide; the nitride is at least one of aluminum nitride, boron nitride, and silicon nitride; the carbide is silicon carbide and / or boron carbide. Nitrides / carbides can increase the thermal conductivity of the use position under the condition of ensuring insulation, thereby playing a role in improving the electrical performance and safety performance of the battery core. The adhesive is at least one of VDF, PAA, and PVA.

[0022] In a second aspect, a second object of the present invention is to provide a method for preparing the short-circuit-proof all-solid-state battery as described above, which comprises the following steps:

[0023] S1. Preparation of positive electrode sheet: evenly coating the positive electrode active material coating slurry and the insulating coating slurry on the surface of the positive electrode current collector, so that the insulating coating is located on both sides of the positive electrode active material coating in the width direction, baking until the weight loss rate is less than 0.2%, and obtaining the positive electrode sheet after compaction and die cutting;

[0024] S2. Preparation of negative electrode sheet: uniformly coating the negative electrode active material coating slurry on the surface of the negative electrode current collector, and baking until the weight loss rate is less than 0.4%; coating the solid electrolyte layer slurry on the negative electrode sheet and covering the negative electrode active material coating, and obtaining the negative electrode sheet coated with the solid electrolyte layer after compaction and die cutting;

[0025] S3, preparation of a semi-finished core product: laminating the positive electrode sheet obtained in step S1 and the negative electrode sheet obtained in step S2, and pre-combining them by hot pressing to obtain a semi-finished core product;

[0026] S4, preparation of the core body: placing the core body semi-finished product obtained in step S3 in a mold, injecting composite insulating adhesive into the mold and then baking it, so that a composite insulating adhesive layer is formed on both sides of the core body semi-finished product in the length direction, thereby obtaining the core body;

[0027] S5. Preparation of an all-solid-state battery: The core obtained in step S4 is packaged and pressed to obtain the short-circuit-proof all-solid-state battery.

[0028] As a preferred embodiment of the present invention, the number of layers of positive electrode sheets in the core semi-finished product of step S3 is n, and the number of layers of negative electrode sheets is n+1; the pre-composite hot pressing temperature is 45-100° C., and the hot pressing pressure is 3-10 MPa.

[0029] As a preferred embodiment of the present invention, the baking temperature in step S4 is 50-80° C. and the baking time is 10-20 min.

[0030] As a preferred embodiment of the present invention, the pressing pressure in step S5 is 300-600 MPa and the pressing time is 1-3 min.

[0031] The all-solid-state battery of the present invention can be an all-solid-state sodium ion battery or an all-solid-state lithium ion battery. The electrode sheet structure and battery composition of the present invention can be adapted, and the specific type depends on the selection of positive and negative active materials.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] 1. The present invention coats an insulating coating on the positive electrode plate, and makes the upper and lower end edges of the negative electrode active material coating of the negative electrode plate after lamination be located in the insulating coating. On the one hand, it can ensure insulation and effectively reduce or avoid the possibility of direct contact between the positive and negative electrode plates and thus causing a battery short circuit due to burrs, edge cracks, etc. of the plate, thereby improving the safety of the battery and reducing the risk of thermal runaway and fire caused by short circuit. On the other hand, the insulating coating can increase flexibility and mechanical strength.

[0034] 2. The present invention further improves the insulation of the all-solid-state battery by arranging a composite insulating adhesive layer on both sides of the core in the length direction. At the same time, the composite insulating adhesive layer can increase the thermal conductivity of the core.

[0035] 3. The preparation method of the present invention has simple process steps, simplifies the process of battery manufacturing, reduces the difficulty of battery design and manufacturing, reduces production costs and improves production efficiency, is very suitable for commercialization and large-scale production, paves the way for the commercialization and large-scale application of all-solid-state battery technology, and is conducive to promoting the advancement of clean energy storage technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 It is a schematic diagram of the structure of the positive electrode membrane in the preparation method of the present invention;

[0037] Figure 2 It is a schematic diagram of the structure of the positive electrode sheet in the preparation method of the present invention;

[0038] Figure 3 is a schematic structural diagram of the negative electrode membrane in the preparation method of the present invention;

[0039] Figure 4 It is a schematic diagram of the structure of the negative electrode sheet in the preparation method of the present invention;

[0040] Figure 5 It is a structural schematic diagram of the core semi-finished product in the preparation method of the present invention;

[0041] Figure 6 It is a structural schematic diagram of the semi-finished core product in the preparation method of the present invention being placed in a mold;

[0042] Figure 7 is a schematic structural diagram of the all-solid-state battery in the preparation method of the present invention;

[0043] Explanation of the accompanying drawings: 100, positive electrode membrane; 110, positive electrode plate; 111, positive electrode ear; 112 and 114, insulating coating; 113, positive electrode active material coating; 200, negative electrode membrane; 210, negative electrode plate; 211, negative electrode ear; 212, negative electrode active material coating; 300, core semi-finished product; 400, core; 500, all-solid-state battery; 510, composite insulating adhesive layer. DETAILED DESCRIPTION

[0044] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0045] A short-circuit-proof all-solid-state battery, comprising a core body, wherein the core body comprises a positive electrode sheet, a solid electrolyte layer and a negative electrode sheet stacked in sequence;

[0046] The positive electrode sheet comprises a positive electrode current collector, a positive electrode ear arranged at the end of the positive electrode current collector, and a positive electrode active material coating and an insulating coating formed on the surface of the positive electrode current collector, wherein the insulating coating is located at the upper and lower ends of the positive electrode active material coating, that is, between the positive electrode active material coating and the positive electrode ear, and on the side of the surface of the positive electrode current collector away from the positive electrode ear;

[0047] The negative electrode sheet includes a negative electrode current collector, a negative electrode ear arranged at the end of the negative electrode current collector, and a negative electrode active material coating formed on the surface of the negative electrode current collector;

[0048] The upper and lower ends of the negative electrode active material coating are respectively located in the two insulating coatings;

[0049] The core body is provided with composite insulating adhesive layers on both sides in the length direction.

[0050] The length a of the negative electrode active material coating and the length a' of the positive electrode active material coating and the length c' of the insulating coating are in the following relationship: a'<a<a'+2c; the width b of the negative electrode active material coating and the width b' of the positive electrode active material coating are in the following relationship: b'<b. Specifically, the length a of the negative electrode active material coating and the length a' of the positive electrode active material coating are in the following relationship: a-a'=2~4mm. The width b of the negative electrode active material coating and the width b' of the positive electrode active material coating are in the following relationship: b-b'=1~3mm. The length c' of the insulating coating is 2~6mm. The thickness of the insulating coating is the same as that of the positive electrode active material coating, and the thickness of the insulating coating is specifically 50~500um.

[0051] The insulating coating includes an adhesive, an inorganic oxide and an insulating paint, and the mass percentage of the adhesive, the inorganic oxide and the insulating paint is 10% to 30%: 40% to 50%: 30% to 40%. The molecular weight of the adhesive is 500,000 to 1,000,000, and the adhesive is at least one of PVDF, PAA and PVA; the inorganic oxide is nano-alumina and / or nano-ceramic powder; and the insulating paint is at least one of polyester resin, polyacetyl phthalimide resin, polyurethane and epoxy resin.

[0052] The composite insulating adhesive layer includes nano inorganic oxide, glass fiber, nitride / carbide, and adhesive, wherein "nitride / carbide" is nitride or carbide. The mass percentage of nano inorganic oxide, glass fiber, nitride / carbide and adhesive is 30% to 40%: 20% to 30%: 10% to 20%: 20% to 30%.

[0053] The above-mentioned method for preparing the short-circuit-proof all-solid-state battery comprises the following steps:

[0054] S1. Preparation of positive electrode sheet: Use a double planetary mixer to mix the positive electrode active material coating slurry and the insulating coating slurry evenly. Figure 1 As shown, the positive electrode active material coating slurry and the insulating coating slurry are uniformly coated on the surface of the positive electrode current collector, so that the insulating coating is located on both sides of the positive electrode active material coating in the width direction, and baked until the weight loss rate is less than 0.2%, to obtain a positive electrode film 100; wherein, the positive electrode active material coating slurry is coated on the positive electrode current collector 101 area, the insulating coating slurry is coated on the positive electrode current collector 102 and 104 areas, and the blank current collector 103 area is used as the pole piece ear 111 die cutting position. Figure 2As shown, the positive electrode film 100 is compacted by a roller press and then die-cut by a die-cutting machine of a specific size to obtain a positive electrode sheet 110. The length of the insulating coating regions 112 and 114 is c'=d'=2-6 mm.

[0055] S2. Preparation of negative electrode sheet: Use a double planetary mixer to mix the negative electrode active material coating slurry evenly. Figure 3 As shown, the negative electrode active material coating slurry is evenly coated on the negative electrode current collector surface 202 area to form a negative electrode active material coating, and baked until the weight loss rate is less than 0.4%, thereby obtaining a negative electrode film 200; wherein the blank current collector 201 area is used as the die-cutting position of the pole piece and the pole ear 211. The solid electrolyte layer slurry is coated on the negative electrode film 200 and covers the negative electrode active material coating to obtain a negative electrode film 200 coated with a solid electrolyte layer. Figure 4 As shown, the negative electrode film 200 is compacted by a roller press and then die-cut by a die-cutting machine of a specific size to obtain a negative electrode sheet 210 .

[0056] The length a of the negative electrode active material coating 212 and the length a' of the positive electrode active material coating 113 have the following relationship: a-a'=2-4 mm. The width b of the negative electrode active material coating 212 and the width b' of the positive electrode active material coating 113 have the following relationship: b-b'=1-3 mm.

[0057] S3. Preparation of semi-finished core products: Figure 5 As shown, the positive electrode sheet 110 obtained in step S1 and the negative electrode sheet 210 obtained in step S2 are stacked using a stacking machine, wherein the number of layers of the positive electrode sheet 110 is n, and the number of layers of the negative electrode sheet 210 is n+1. The hot pressing pre-compounding is performed under the conditions of a hot pressing temperature of 45 to 100° C. and a hot pressing pressure of 3 to 10 MPa to obtain a core semi-finished product 300.

[0058] In the semi-finished core 300 , the bottom edge AB of the negative electrode sheet cannot exceed the area of ​​the positive electrode sheet 302 , and the top edge CD of the negative electrode sheet cannot exceed the area of ​​the positive electrode sheet 301 .

[0059] S4. Preparation of core: Figure 6 As shown, the core semi-finished product 300 obtained in step S3 is placed in a mold, and composite insulating glue is injected into the side insulating area 1 and the side insulating area 2 in the mold, and baked at a temperature of 50 to 80° C. for 10 to 20 minutes to form a composite insulating glue layer 510 on both sides of the core semi-finished product 300 in the length direction, thereby obtaining a core 500;

[0060] S5. Preparation of all-solid-state batteries: Figure 7As shown, the core 500 obtained in step S4 is packaged with an aluminum-plastic film and then pressed in an isostatic pressing device at a pressure of 300 to 600 MPa for 1 to 3 minutes to obtain a short-circuit-proof all-solid-state battery.

[0061] Example 1

[0062] A short-circuit-proof all-solid-state battery, referring to Figure 1 to Figure 7 , which is prepared according to the following steps:

[0063] S1. Preparation of positive electrode sheet

[0064] A double planetary mixer is used to mix the positive electrode active material coating slurry and the insulating coating slurry. The mass percentage composition of the positive electrode active material coating component is as follows: positive electrode active material (LiNi8Co1Mn1O2) 82.5%, conductive agent (SP1.5% + CNTs1.5%) 3%, adhesive (PVDF) 2.5%, solid electrolyte (PEO6% + Li2S-P2S5-LiCl6%) 12%. The mass percentage composition of the insulating coating component is as follows: PVDF 10%, boehmite 50%, polyurethane insulating paint 40%. The positive electrode active material coating component and the insulating coating component are both made into slurry after adding the solvent n-heptane.

[0065] The positive electrode active material coating slurry and the insulating coating slurry are uniformly coated on the surface of the positive electrode current collector (12um aluminum foil) using an extrusion coating machine, so that the insulating coating is located on both sides of the positive electrode active material coating in the width direction, and baked until the weight loss rate is less than 0.2%, to obtain a positive electrode film 100; wherein, the positive electrode active material coating slurry is coated on the 101 area of ​​the positive electrode current collector, and the coating thickness is 300um; the insulating coating slurry is coated on the 102 and 104 areas of the positive electrode current collector, and the coating thickness is 300um; the blank current collector 103 area is used as the die-cutting position of the pole piece and the pole ear 111. After the positive electrode film 100 is compacted by a roller press, it is die-cut using a die-cutting machine of a specific size to obtain a positive electrode sheet 110. Among them, the length of the insulating coating area 112 and 114 is c'=d'=4mm.

[0066] S2. Preparation of negative electrode sheet: Use a double planetary mixer to mix the negative electrode active material coating slurry evenly. Among them, the mass percentage composition of the negative electrode active material coating components is as follows: negative electrode active material (graphite 43% + nano silicon 43%) 86%, conductive agent (SP1% + CNTs1%) 2%, binder (PVDF) 2%, solid electrolyte (PEO 5% + Li2S-P2S5-LiCl5%) 10%. The negative electrode active material coating components are added with solvent n-heptane to prepare the negative electrode active material coating slurry.

[0067] The negative electrode active material coating slurry is uniformly coated on the 202 area of ​​the surface of the negative electrode current collector (6um copper foil) using an extrusion coater, with a coating thickness of 200um to form a negative electrode active material coating, and baked until the weight loss rate is less than 0.4%, to obtain a negative electrode membrane 200; wherein the blank current collector 201 area is used as the die-cutting position of the pole piece and the pole ear 211. The solid electrolyte layer slurry is coated on the negative electrode membrane 200 and covered with the negative electrode active material coating to obtain a negative electrode membrane 200 coated with a solid electrolyte layer. After the negative electrode membrane 200 is compacted by a roller press, it is die-cut using a die-cutting machine of a specific size to obtain a negative electrode pole piece 210.

[0068] The length a of the negative electrode active material coating 212 is 60 mm, and the length a′ of the positive electrode active material coating 113 is 56 mm. The width b of the negative electrode active material coating 212 is 40 mm, and the width b′ of the positive electrode active material coating 113 is 38 mm.

[0069] S3. Preparation of a semi-finished core product: Ten positive electrode sheets 110 prepared in step S1 and 11 negative electrode sheets 210 prepared in step S2 are stacked using a stacking machine, and hot-pressed at a temperature of 60° C. and a pressure of 5 MPa to prepare a semi-finished core product 300.

[0070] S4, preparation of the core body: placing the core body semi-finished product 300 obtained in step S3 in a mold, injecting composite insulating glue into the side insulating area 1 and the side insulating area 2 in the mold, and baking at a temperature of 60° C. for 15 minutes to form a composite insulating glue layer 510 on both sides of the core body semi-finished product 300 in the length direction, thereby obtaining the core body 500. The mass percentages of nano inorganic oxide (Al2O3), glass fiber, nitride (aluminum nitride), and adhesive (PVDF) in the composite insulating glue layer are 40%:30%:10%:20%.

[0071] S5. Preparation of all-solid-state battery: The core 500 obtained in step S4 is packaged with an aluminum-plastic film and then pressed in an isostatic pressing device at a pressure of 400 MPa for 3 minutes to obtain an anti-short-circuit all-solid-state battery.

[0072] Example 2

[0073] The difference between this embodiment and embodiment 1 is that the active material of the positive electrode membrane in step S1 of this embodiment is NaNi3Fe3Mn3Cu1O2, and the solid electrolyte used is Na3Zr2Si2PO 12 In step S2, the active material used in the negative electrode membrane is hard carbon, and the solid electrolyte is also Na3Zr2Si2PO 12 , that is, the all-solid-state battery assembled in this embodiment is an all-solid-state sodium ion battery.

[0074] The rest is the same as in Example 1 and will not be described again here.

[0075] Example 3

[0076] The difference between this embodiment and embodiment 2 is that the active material of the positive electrode membrane in step S1 of this embodiment is sodium iron pyrophosphate.

[0077] The rest is the same as in Example 2 and will not be described again here.

[0078] Example 4

[0079] The difference between this embodiment and the first embodiment is that in step S3 of this embodiment, the lengths c' and d' of the insulating regions 112 and 114 of the positive electrode sheet 110 are both 2 mm; and the difference between the length a' of the positive electrode sheet 110 and the length a of the negative electrode sheet 210 is also 2 mm.

[0080] The rest is the same as in Example 1 and will not be described again here.

[0081] Example 5

[0082] The difference between this embodiment and embodiment 1 is that the mass percentages of the adhesive, the inorganic oxide and the insulating paint in the insulating paste of step S1 of this embodiment are 30%:40%:30%.

[0083] The rest is the same as in Example 1 and will not be described again here.

[0084] Example 6

[0085] The difference between this embodiment and embodiment 1 is that the mass percentages of nano inorganic oxide, glass fiber, nitride and adhesive in the composite insulating adhesive in step S4 of this embodiment are 30%:20%:20%:30%.

[0086] The rest is the same as in Example 1 and will not be described again here.

[0087] Comparative Example 1

[0088] The difference between this comparative example and Example 1 is that the length c' and the length d' of the insulating coating region 112 and 114 of the positive electrode plate 110 in step S1 of this comparative example are 0 mm.

[0089] The rest is the same as in Example 1 and will not be described again here.

[0090] Comparative Example 2

[0091] The difference between this comparative example and Example 1 is that the width c' of the insulating coating area of ​​the positive electrode plate 110 in step S1 of this comparative example is 0 mm.

[0092] The rest is the same as in Example 1 and will not be described again here.

[0093] Comparative Example 3

[0094] The difference between this comparative example and Example 1 is that the width d′ of the insulating coating region 114 of the positive electrode plate 110 in step S1 of this comparative example is 0 mm.

[0095] The rest is the same as in Example 1 and will not be described again here.

[0096] Comparative Example 4

[0097] The difference between this comparative example and Example 1 is that in step S1 of this comparative example, the foil is not coated with the insulating coating slurry.

[0098] The rest is the same as in Example 1 and will not be described again here.

[0099] Comparative Example 5

[0100] The difference between this comparative example and Example 1 is that in step S4 of this comparative example, no composite insulating glue is injected to prepare the core.

[0101] The rest is the same as in Example 1 and will not be described again here.

[0102] Comparative Example 6

[0103] The difference between this comparative example and Example 1 is that the mass percentages of the adhesive, the inorganic oxide and the insulating paint in the insulating coating slurry in step S1 of this comparative example are 40%:35%:25%.

[0104] The rest is the same as in Example 1 and will not be described again here.

[0105] Comparative Example 7

[0106] The difference between this comparative example and Example 1 is that the mass percentages of nano-inorganic oxide, glass fiber, nitride and adhesive in the composite insulating adhesive in step S4 of this comparative example are 20%:40%:25%:15%.

[0107] The rest is the same as in Example 1 and will not be described again here.

[0108] All-solid-state battery performance test

[0109] The all-solid-state batteries prepared in the above-mentioned Examples 1 to 6 and Comparative Examples 1 to 7 were subjected to performance tests, including battery impedance, rate and insulation Hi-pot tests. The specific methods are as follows:

[0110] Impedance test method: adjust the battery SOC to 50% at 0.5C current, leave for 2h, record the voltage U0, discharge at 1.5C constant current for 30s, record the voltage U1; calculate DCR as: (U0-U1) / I (1.5C) .

[0111] Rate test method: charge with 0.5C current to the upper cut-off voltage; leave for 30 minutes; discharge with 0.2C current to the lower cut-off voltage, record the capacity C0; leave for 30 minutes; charge with 0.5C current to the upper cut-off voltage; leave for 30 minutes; discharge with 1C current to the lower cut-off voltage, record the capacity C1; calculate the rate retention rate: (C1 / C0*100%).

[0112] Insulation Hi-pot test method: Perform Hi-pot test on 100pcs of all-solid-state batteries. The test conditions are delay time 1.5s, test time 4.0s, test pressure 10MPa, and test voltage 250V; record the number of OK as M; calculate the excellence rate P: (M / 20*100%).

[0113] The test results are shown in Table 1.

[0114] Table 1 Test data of each group of embodiments and comparative examples

[0115]

[0116]

[0117] It can be seen from the test data in Table 1 that all the embodiments of the present invention and the solutions in the comparative examples have basically no effect on the battery DCR and rate, but the all-solid-state batteries prepared in Examples 1 to 6 have excellent short-circuit protection performance, and the all-solid-state batteries prepared in Comparative Examples 1 to 7 have obviously higher short-circuit rates, indicating that the present invention effectively reduces or avoids the possibility of battery short circuit due to burrs, edge ruptures, etc. of solid-state battery pole pieces by controlling the edges of both ends of the negative electrode pole piece to be located in the insulating coating of the positive electrode pole piece and injecting composite insulating glue on the side of the core body, thereby improving the safety of the battery and reducing the risk of thermal runaway and fire caused by short circuit.

[0118] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.

Claims

1. A short-circuit-proof all-solid-state battery, characterized in that: The core body comprises a positive electrode sheet, a solid electrolyte layer and a negative electrode sheet which are stacked in sequence; The positive electrode plate includes a positive electrode current collector and a positive electrode active material coating and an insulating coating formed on the surface of the positive electrode current collector, wherein the insulating coating is located at the upper and lower ends of the positive electrode active material coating; the negative electrode plate includes a negative electrode current collector and a negative electrode active material coating formed on the surface of the negative electrode current collector; The upper and lower ends of the negative electrode active material coating are respectively located in the two insulating coating areas of the positive electrode plate; The core body is provided with composite insulating adhesive layers on both sides in the length direction.

2. The short-circuit-proof all-solid-state battery according to claim 1, characterized in that: The length a of the negative electrode active material coating and the length a' of the positive electrode active material coating and the length c' of the insulating coating are in the following relationship: a'<a<a'+2c; the width b of the negative electrode active material coating and the width b' of the positive electrode active material coating are in the following relationship: b'<b.

3. The short-circuit-proof all-solid-state battery according to claim 1 or 2, characterized in that: The insulating coating comprises an adhesive, an inorganic oxide and an insulating paint, wherein the mass percentages of the adhesive, the inorganic oxide and the insulating paint are 10% to 30%: 40% to 50%: 30% to 40%.

4. The short-circuit-proof all-solid-state battery according to claim 3, characterized in that: The molecular weight of the adhesive is 500,000 to 1,000,000; the inorganic oxide is nano-alumina and / or nano-ceramic powder; and the insulating paint is at least one of polyester resin, polyacetylphthalimide resin, polyurethane and epoxy resin.

5. The short-circuit-proof all-solid-state battery according to claim 3, characterized in that: The thickness of the insulating coating is the same as that of the positive electrode active material coating; the thickness of the insulating coating is 50 to 500 um.

6. The short-circuit-proof all-solid-state battery according to claim 1 or 2, characterized in that: The composite insulating adhesive layer comprises nano inorganic oxide, glass fiber, nitride / carbide and adhesive, and the mass percentage of the nano inorganic oxide, glass fiber, nitride / carbide and adhesive is 30%-40%: 20%-30%: 10%-20%: 20%-30%.

7. A method for preparing a short-circuit-proof all-solid-state battery according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Preparation of positive electrode sheet: evenly coating the positive electrode active material coating slurry and the insulating coating slurry on the surface of the positive electrode current collector, so that the insulating coating is located on both sides of the positive electrode active material coating in the width direction, baking until the weight loss rate is less than 0.2%, and obtaining the positive electrode sheet after compaction and die cutting; S2. Preparation of negative electrode sheet: uniformly coating the negative electrode active material coating slurry on the surface of the negative electrode current collector, and baking until the weight loss rate is less than 0.4%; coating the solid electrolyte layer slurry on the negative electrode sheet and covering the negative electrode active material coating, and obtaining the negative electrode sheet coated with the solid electrolyte layer after compaction and die cutting; S3, preparation of a semi-finished core product: laminating the positive electrode sheet obtained in step S1 and the negative electrode sheet obtained in step S2, and pre-combining them by hot pressing to obtain a semi-finished core product; S4, preparation of the core body: placing the core body semi-finished product obtained in step S3 in a mold, injecting composite insulating adhesive into the mold and then baking it, so that a composite insulating adhesive layer is formed on both sides of the core body semi-finished product in the length direction, thereby obtaining the core body; S5. Preparation of an all-solid-state battery: The core obtained in step S4 is packaged and pressed to obtain the short-circuit-proof all-solid-state battery.

8. The method for preparing a short-circuit-proof all-solid-state battery according to claim 7, characterized in that: The number of layers of positive electrode sheets in the core semi-finished product of step S3 is n, and the number of layers of negative electrode sheets is n+1; the hot pressing temperature of the pre-composite is 45-100° C., and the hot pressing pressure is 3-10 MPa.

9. The method for preparing a short-circuit-proof all-solid-state battery according to claim 7, characterized in that: The baking temperature in step S4 is 50-80° C. and the baking time is 10-20 min.

10. The method for preparing a short-circuit-proof all-solid-state battery according to claim 7, characterized in that: The pressing pressure in step S5 is 300-600 MPa and the pressing time is 1-3 min.

Citation Information

Patent Citations

  • Anti-short-circuit solid-state battery and preparation method thereof

    CN115513532A

  • Short-circuit-proof all-solid-state battery and preparation method thereof

    CN118213607A